The effect of Stylistic Discovery Directed and Programmed Education on teaching some football skills and understand the benefits of physical education and health - Ahmed Zuhair Kattan 1 , Ahmed Hussein Abd 2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The guided discovery method is one of the teaching methods that work to engage the student in the discoveryprocess, and the essence of this method is the special relationship that arises between the teacher and thestudent through which leads the successive questions that the teacher directs to reach the answers that thestudent performs that correspond to these questions, if every question the teacher directs leads to one correctresponse that the student will discover, and if the accumulation of this process occurs. the researchers used thestatistical bag (SPSS) through which the statistical methods were used, the most important of which were: (t)test for the interlinked samples and the L.S .D test and through the results reached the researchers concludeda set of conclusions, the most important of which : The use of the two methods of directed discovery andprogrammed education and the method followed by the teacher have a positive effect in teaching some basicskills in football, as well as the method of directed discovery over the style of programmed education andthe method followed by the teacher in teaching some of the skills under discussion.